Stabilitas Mikrob Usus, Histologi Hati dan Ginjal Mencit Setelah Pemberian Ekstrak Pliek u Bumbu Masak Tradisional Aceh (STABILITY OF GUT MICROBIAL AND HISTOLOGY OF LIVER AND KIDNEY OF MICE AFTER ADMINISTRATION OF PLIEK-U EXTRACT - ., Nurliana; Estuningsih, Sri; ., Sugito; Masyitha, Dian (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
Pliek u is one of the traditional spices of Aceh prepared by fermentation of coconut meat which is usedas chicken feed additive too. The stability of gut micro flora and histopathological changes of liver andkidney of mice were detected after three days oral administration of acute single dose of ethanol extract ofpliek u. Nine animals were used and grouped into three; in which group I and II (treatment groups) wereadministered 370 and 733 mg/kg body weight of pliek u, respectively, and group III referred as the control.At the fourth day of experiment, all animals were sacrificed, and their livers, kidneys and intestinal gutwere excised. The gut microbial was measured by Total Plate Count (TPC). Livers and kidneys wereprocessed for paraffin procedure and hematoxyllin-eosin staining. The results showed that the ethanolextract of pliek u has no significant effect (P>0.05) on the TPC of the gut microbial and the structure of theliver and kidney of mice. It can be concluded that administration of the two doses (370 and 730 mg/kg bw)of pliek u did not lowering the numbers of gut microbial and were not toxic to the livers and kidneys of themice.
Keywords: pliek u, gut microbial, histopatology, liver, kidney